2020
DOI: 10.3390/ijms21197300
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Metabolism in the Cerebral Cortex from Several Mice Models during Aging

Abstract: Adenosine is a neuromodulator that has been involved in aging and neurodegenerative diseases as Alzheimer’s disease (AD). In the present work, we analyzed the possible modulation of purine metabolites, 5’nucleotidase (5′NT) and adenosine deaminase (ADA) activities, and adenosine monophosphate (AMP)-activated protein kinase (AMPK) and its phosphorylated form during aging in the cerebral cortex. Three murine models were used: senescence-accelerated mouse-resistant 1 (SAMR1, normal senescence), senescence-acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…Elevated levels of brain cholesterol in the plasma membrane could increase membrane rigidity, which might affect the neurotransmission through a reduction of membrane-associated proteins movement (i.e., neurotransmitters receptors) from and to the synapsis. Notably, we previously found a significant age-dependent reduction in adenosine [ 27 ] and metabotropic glutamate receptors [ 28 ] together with their corresponding endogenous ligand [ 26 ] in SAMP8 mice. In addition, cholesterol modulates adenosine A 2A receptors expressed on the cell surface of in vitro glial cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of brain cholesterol in the plasma membrane could increase membrane rigidity, which might affect the neurotransmission through a reduction of membrane-associated proteins movement (i.e., neurotransmitters receptors) from and to the synapsis. Notably, we previously found a significant age-dependent reduction in adenosine [ 27 ] and metabotropic glutamate receptors [ 28 ] together with their corresponding endogenous ligand [ 26 ] in SAMP8 mice. In addition, cholesterol modulates adenosine A 2A receptors expressed on the cell surface of in vitro glial cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects and mechanisms of resveratrol on aging and age-related diseases, including neurodegenerative disorders, have been reviewed elsewhere [ 24 , 25 ]. Our previous work revealed that RSV supplementation in SAMP8 mice was able to modulate adenosine metabolism [ 26 ] and to modulate and reverse the age-related effect on adenosine-mediated signalling [ 27 ], and that metabotropic glutamate receptors are differently modulated by RSV, depending on age [ 28 ]. Moreover, we have described that a high-fat diet (HFD) and RSV diet modulate adenosinergic signalling in SAMP8 mice by increasing adenosine A 2 receptors and 5′-NT activity [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…All samples were run in duplicate. Sample values were obtained by interpolation in an inosine standard curve performed in parallel on the same plate as previously described ( 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, 100 µM theacrine and 1 µM CGS21680 were used in the following experiments. Adenosine mediates its action via the adenosine 2A receptor coupled primarily to the activation of cAMP, which in turn activates AMP-activated protein kinase (AMPK) [21]. To inspect whether theacrine is an effective antagonist of the adenosine 2A receptor, CGS21680 was employed to activate the adenosine 2A receptor by detecting the level of AMPK phosphorylation (P-AMPK/AMPK) in MCF-7 cells with or without the theacrine supplement (Figure 3).…”
Section: Molecular Modeling Of Theacrine Caffeine and Adenosine Docki...mentioning
confidence: 99%